INCREASING THE MOTIVATION FOR LEARNING FOREIGN LANGUAGE BY USING THE WEB 2.0 APPLICATION PIXTON - Dinko Stratiev (Педагогически форум)
In foreign language teaching digital media is mainly used for acquiring information related mostly to project activities. The article introduces the Pixton Web 2.0 application as a learning tool for communication, production and presentation.